Epidemiology and Genetic Evolutionary Analysis of Influenza Virus Among Children in Hainan Island, China, 2021–2023 - Meng Chang; Shengjie Shi; Yan Jin; Gaoyu Wang; Ruoyan Peng; Jing An; Yi Huang; Xiaoyuan Hu; Chuanning Tang; Yi Niu; Xiuying Tian; Wanxin Deng; et al. (Pathogens)
Background: During the COVID-19 pandemic, we continuously monitored the epidemiology of influenza virus among pediatric patients from January 2021 to December 2023 in Hainan Island, China. Methods: In this study, we collected 54,974 nasopharyngeal swab samples for influenza A Virus (IAV) testing and 53,151 samples for influenza B Virus (IBV) testing from pediatric outpatients. Additionally, we also collected 19,687 nasopharyngeal swab samples from pediatric inpatients for IAV and IBV testing. Outpatient samples were screened for influenza viruses (IVs) infection by the colloidal gold method. Targeted Next-Generation Sequencing (tNGS) was used to detect influenza virus infections in inpatients. Influenza virus types were identified by analyzing the HA/NA partial regions. Results: The findings revealed a significant decrease in the infection rate of IBV over the specified period, while the infection rate of IAV exhibited a rising trend. Additionally, B/Victoria lineage was the dominant epidemic strain in 2021, while the epidemic strains in 2022 and 2023 underwent a dynamic transformation from A/H3N2 to A/H1N1. Phylogenetic analysis revealed close relationships among the circulating strains. Nonetheless, because the sample size is limited, additional research is required. Conclusions: Our findings suggest that the predominant types of influenza viruses in the pediatric population are undergoing dynamic changes, influenced by the implementation and relaxation of non-pharmaceutical intervention measures. These findings highlight the need for adaptive influenza vaccination and containment strategies, particularly in tropical regions like Hainan, where climate and public health policies significantly impact viral transmission patterns. The insights gained from this study could inform more effective public health strategies in similar regions to mitigate the impact of influenza outbreaks in the future.